Synthesis of fatty acid methyl esters from pomace oil catalyzed by zinc stearate: A kinetic study of the transesterification and esterification reactions - Alvarez Serafini, Mariana Soledad (2019)
In this work, the simultaneous transesterification and esterification reactions of olive pomace oil with methanol catalyzed by zinc stearate were studied. This catalyst is a crystalline solid at room temperature, but it is soluble in the reaction medium at reaction temperature. Zinc stearate has surfactant properties that cause the formation of an emulsion in the reaction system. The stability of the emulsion formed in the oil-methanol-catalyst system was compared to that in the FAME (fatty acid methyl esters)-methanol-catalyst system. It was observed that the emulsion formed in the presence of high amounts of FAME is much more unstable, which makes the catalyst easy to separate from the reaction products. The kinetics of esterification and transesterification were also studied. All the kinetic and equilibrium constants were determined with a complete model, considering the three stepwise reactions corresponding to the transesterification of triglycerides and the esterification of free fatty acids. The parameters obtained were used to model the operating conditions that would allow obtaining biodiesel that meets the quality standards.